Euzebiusza z Cezarei polemika z ideałem theios aner - Kotłowska, Anna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
This article contains an analysis of Eusebius of Caesarea’s response to the Lover of Truth written by Sossianus Hierocles.

Eusebius of Caesarea, a great scholar, “son of Pamphilus”, was one of the most influential persons during the first half of the fourth century AD in the Roman Empire. He was active as a bishop, theologian, politician and historian. Among his numerous literary works (six volumes of Patrologia Graeca) we are interested in a short polemical treatise, entitled Contra Hieroclem. Sossianus Hierocles, successively praeses of Palmyra and Bithynia, vicarius Orientis, praefectus Aegypti, about the year 303 wrote a criticism on the claims of the Christians, lost pamphlet in two books, called Philalethes. In part of his paper, concerning wonderful works of Apollonius, Hierocles used Philostratus’ Vita Apollonii. Contra Hieroclem is a response to the Lover of Truth. The goal of treatise of Eusebius is remarkable. He applied his critical faculties on the documents which relate to the wonderful things, “miracles”, ascribed to Apollonius. Eusebius recognized without difficulty and aversion that Apollonius was a wise man worthy of admiration; he admitted also everything that was told about Apollonius’ piety, teachings, asceticism. Bishop of Caesarea rejected however the miraculous prodigies that were assigned to Master of Tyana, not only assigning them to magic and daemons, but rather explaining in the way of euhemerism.
Eusebius of Caesarea’s polemics with the ideal of theios aner
Keywords: Apollonius of Tyana; Eusebius of Caesarea; Christian Apologetic; Sossianus Hierocles